Sepsis in Obstetrics: Pathophysiology and Diagnostic Definitions. Issue 4 (July 2017) - Parfitt, Sheryl E.; Bogat, Mary L.; Hering, Sandra L.; Roth, Cheryl
Abstract : Abstract: In spite of many medical breakthroughs, sepsis continues to be challenging to identify, treat, and successfully resolve, including among the obstetric population. Sepsis is the result of an overactive, complex inflammatory response that is not completely understood. Currently there are no nationally agreed-upon criteria for systemic inflammatory response syndrome or sepsis in pregnant or peripartum women, as the physiologic changes of pregnancy have not been taken into consideration. This article is the first in a series of three that discuss the importance of sepsis and septic shock in pregnancy. The focus of this article is to understand the proposed pathophysiology of sepsis and new definitions associated with sepsis and septic shock. Knowledge of these conditions can assist in better identification of sepsis in the obstetric population. Abstract : Sepsis in obstetrics can be challenging to identify in a timely manner so that appropriate treatment can be initiated within the first crucial hours to promote a positive outcome. The proposed pathophysiology of sepsis, new definitions associated with sepsis and septic shock, and application to maternity care are presented.